"Paper cadavers: the archives of dictatorshio in Guatemala", de Kirsten Weld - Pimentel Chacón, Jonathan (Anuario de Estudios Centroamericanos, 2016)
Resumen del libro "Paper cadavers: the archives of dictatorshio in Guatemala", de Kirsten Weld